2018
DOI: 10.1159/000492119
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Surgical Volume on Perioperative and Oncological Outcomes Following Radical Prostatectomy

Abstract: Introduction: The purpose of this study was to evaluate whether the number of radical prostatectomies per hospital per year is associated with stage distribution, surgical techniques or quality related outcome in Germany. Materials and Methods: A German Internet-based database was analyzed. Hospitals were categorized according to their yearly radical prostatectomy (RP) volume. Patient’s characteristics, RP techniques, and outcome-related parameters were compared between the different hospital volume categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Before 2017 selection for NVBP was based on preoperative and intraoperative findings such as digital rectal examination, number and location of positive biopsies, preoperative PSA and if available MRT findings. Furthermore, results of high-volume centers are not necessarily applicable to low-volume care provider, which might limit the generalizability of our findings (27). Finally, our data do not provide data about patient's comorbidities.…”
Section: Discussionmentioning
confidence: 75%
“…Before 2017 selection for NVBP was based on preoperative and intraoperative findings such as digital rectal examination, number and location of positive biopsies, preoperative PSA and if available MRT findings. Furthermore, results of high-volume centers are not necessarily applicable to low-volume care provider, which might limit the generalizability of our findings (27). Finally, our data do not provide data about patient's comorbidities.…”
Section: Discussionmentioning
confidence: 75%
“…This is significant because comprehensive cancer centers perform higher volumes of complex cancer surgeries and have lower perioperative complications. [19][20][21] For patients, this is an incentive to receive care at a comprehensive cancer center even if it means traveling a significant distance.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Comprehensive centers perform higher volumes of complex cancer surgeries, which is associated with lower perioperative complications. 19 - 21 A recent study found a greater distance from the patient’s home, race/ethnicity, lack of private insurance and low socioeconomic status were independent barriers to receiving treatment at one of these centers 18 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that surgical skill level and overall case volume can impact oncological outcomes in cancer surgery. [34][35][36] The amount and type of opioids, COX inhibitors, local anesthetics, and beta blockade required, if these agents are used at all, will also vary among patients. If used, the amount of inhaled volatile agent required will also differ by patient and is impacted by the use of regional anesthesia, opioids, neuromuscular blockade, neoadjuvant non-opioid pain medications, and patient-specific factors.…”
Section: ) Disseminaɵon In the Circulaɵonmentioning
confidence: 99%